His Bundle Extrasystole or A Dual Atrioventricular Nodal Response - Akbarzadeh, Mohammad Ali (International Journal of Cardiovascular Practice, 2018)
A dual atrioventricular (AV) nodal response and His bundle extrasystole cannot be different in many cases with certainty. We present a 31-year-old man with episodes of palpitation and conducted and non-conducted His bundle extrasystole detected during an electrophysiology study.